THE GLUTEN – FREE DIET BEYOND CELIAC DISEASE: TRENDS, RISKS AND NUTRITIONAL DEFICIENCIES - Aleksandra Klukowska; Marta Danuta Cendrowska; Łukasz Brzost; Beata Choromańska; Julia Maszewska; Szymon Milnerowicz; Julia Procyk; Barbara Ponitka; Karolina Stępień; Justyna Berent; Paulina Rzepa; Wiktoria Szumlińska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Gluten-free diet is effective treatment for celiac disease patients. However, the gluten-free diet has become increasingly popular in recent years, not only as a medical intervention for celiac disease but also as a lifestyle preference for individuals who perceive it as a healthier option. Additionally, there has been a growing number of studies investigating the use of gluten-free diets in the management of various medical conditions. Nevertheless, there are growing concerns regarding possible nutritional deficiencies associated with the exclusion of gluten-containing grains, as well as skepticism regarding the purported health benefits of a gluten-free diet in individuals without diagnosed gluten-related disorders. Aim of the study: We aimed to systematically review the current knowledge about nutritional deficiencies and risks associated with gluten-free diet. Methodology: An extensive search was conducted using electronic database PubMed to identify relevant studies published between 2010 and 2025. The search was based on keywords such as: ‘gluten-free diet’, ‘celiac disease,’ ‘nutritional deficiencies,’ and ‘diet therapy,’. Results and Discussion: Analysis of existing research suggests that individuals adhering to a gluten-free diet may be prone to inadequate intake of dietary fiber and several key micronutrients, including vitamins D, E, and B-group, along with critical minerals such as iron, zinc, calcium, and magnesium. Additionally, those consuming an imbalanced gluten-free diet often have a higher intake of total fat, particularly saturated fatty acids and cholesterol. Conclusion: Current research indicates that adherence to a gluten-free diet is associated with specific micronutrient deficiencies. Individuals complying with this dietary regimen should be informed of the potential nutritional risks and adopt strategies to maintain an adequate and balanced nutrient intake. Clinical dietary oversight is recommended to identify and address common deficiencies linked to gluten exclusion.